Handbook of ventilation technology for the built environment design, control and testing - Cao, Shi-Jie; Feng, Zhuangbo (IET built environment series, 2021)
This comprehensive research reference summarises and presents the state-of-the-art methods for building ventilation design and control. Cutting-edge research achievements are introduced, including fast ventilation predictions, online monitoring and intelligent control, coupled simulation of urban simulation, and CFD-based adjoint design